2017
DOI: 10.1149/2.1361704jes
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrochemical Preparation of Ni-Cr Alloy from Solid Oxides in Molten CaCl2

Abstract: Direct electro-reduction of mixed powders of chromium oxide (Cr 2 O 3 ) and nickel oxide (NiO) to the intermetallic compound Cr 1.12 Ni 2.88 was successfully demonstrated in CaCl 2 molten salt at 900 • C. The reduction mechanism was investigated by cyclic voltammetry using a metallic cavity electrode (MCE) as well as the characterizations of some partially electrolyzed products and Ni-Cr alloy prepared from constant voltage electrolysis by terminating the reduction process after different times, which were cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Liu et al studied the electroreduction behaviour of NiO in Mo-CE in CaCl 2 melt at 900 °C by cyclic voltammetry and reported the reduction potential of NiO as 1.5 V (vs Ca 2+ |Ca). 59 Qiu et al also probed into the reduction phenomenon of NiO in molten CaCl 2 using Mo cavity electrodes by cyclic voltammetry technique. 60 In the study, the reduction of NiO was found to occur at 0.8 V (vs Ca 2+ |Ca) in Mo-CE with one mechanically drilled hole and at 1.1 V (vs Ca 2+ |Ca) in Mo-CE with two laser-drilled holes.…”
Section: Characterization Of the Sintered Mixedmentioning
confidence: 99%
“…Liu et al studied the electroreduction behaviour of NiO in Mo-CE in CaCl 2 melt at 900 °C by cyclic voltammetry and reported the reduction potential of NiO as 1.5 V (vs Ca 2+ |Ca). 59 Qiu et al also probed into the reduction phenomenon of NiO in molten CaCl 2 using Mo cavity electrodes by cyclic voltammetry technique. 60 In the study, the reduction of NiO was found to occur at 0.8 V (vs Ca 2+ |Ca) in Mo-CE with one mechanically drilled hole and at 1.1 V (vs Ca 2+ |Ca) in Mo-CE with two laser-drilled holes.…”
Section: Characterization Of the Sintered Mixedmentioning
confidence: 99%